Autoimagem, ativismo online e o corpo feminino em performance: recepção a partir de vídeos da tag “Tour pelo meu corpo” no YouTube - Prado, Beatriz de Almeida (2021)
Digital Culture is proving to be a viable and more accessible alternative for many women, teenagers and girls to communicate and organize collectively. Pages and groups that bring reports of experiences and questions on social networks such as YouTube, Facebook and Instagram have been increasing in number and importance, easing the exchange of knowledge, sharing experiences and mutual help between women in an environment that is mainly characterized by the possibility of interactivity. Recognizing that the message shared on the internet can affect the lives and self-esteem of people inside and outside the digital environment, both positively and negatively, this research proposes to investigate the reception of the performances of Tour Pelo Meu Corpo performed by Luíza Junqueira and Ellora Haonne on YouTube to understand how these are interconnected to the body self-image of their audiences and how the processes of body acceptance can change based on these performances. The main objective of this research is to understand how the experience with these performances can modify the spectators' body self- perception and spawn reflections about aesthetic standards, as well as the relationship established by women between self-image and aesthetic standards. It is a qualitative research, which uses media ethnography for data collection and pursuit to categorize the results obtained stem from Hall's studies. As a result, it was realized that, when performing these tours over their own bodies, the YouTubers perform a kind of self-writing, using the videos as an instrument of self-knowledge and confronting an excluding beauty standard, but by publishing these videos online their reflections can become a starting point for questioning the idea of a single kind of body as an ideal, just as rethinking their relationships with their own bodies. It is still not possible to know to what extent the experience with these performances would be able to promote lasting changes regarding the body self-image of girls and women, which are the focus of this study, however, its potential in fostering the discussion can already be seen. on aesthetic standards for the female body, intending to continue the study in future research.